A Fragile Balance
DOI: 10.1057/9781137482372.0009
|View full text |Cite
|
Sign up to set email alerts
|

Refund to Savings

Abstract: Can low-cost, scalable interventions increase saving at tax time? 2) Does the application of behavioral economics principles increase saving? 3) Do tax-time savings persist over time and improve the balance sheet of households? Randomized Experiments All R2S research is carried out in randomized experiments. Randomized experiments are the gold standard for social science evidence. Any observed differences in outcome attributable to the intervention. 2011 Research Activities In 2011, R2S developed and piloted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Similarly, many families lack emergency savings, and this makes it difficult for them to cope with common financial exigencies such as a car repair or a trip to the hospital (Grinstein‐Weiss et al ). Half of American households—and 60% of low‐income households—report that they could not come up with $2,000 in an emergency (Grinstein‐Weiss et al ; Lusardi, Schneider, and Tufano ; see also FINRA Investor Education Foundation ). Without stored liquid assets, households often turn to costly alternative financial services, sometimes transforming a minor emergency into a major financial setback (Shah, Mullainathan, and Shafir ).…”
Section: Three Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, many families lack emergency savings, and this makes it difficult for them to cope with common financial exigencies such as a car repair or a trip to the hospital (Grinstein‐Weiss et al ). Half of American households—and 60% of low‐income households—report that they could not come up with $2,000 in an emergency (Grinstein‐Weiss et al ; Lusardi, Schneider, and Tufano ; see also FINRA Investor Education Foundation ). Without stored liquid assets, households often turn to costly alternative financial services, sometimes transforming a minor emergency into a major financial setback (Shah, Mullainathan, and Shafir ).…”
Section: Three Trendsmentioning
confidence: 99%
“…The receipt of a large refund at tax time, owing to the Earned Income Tax Credit or the Child Tax Credit, provides another opportunity for families to learn about and accumulate savings (Romich et al ). The Refund to Savings initiative, for example, uses a free electronic tax‐filing platform to help low‐income households convert tax‐refund windfalls, such as those from the Earned Income Tax Credit, into savings (Grinstein‐Weiss et al ).…”
Section: Action For Financial Capabilitymentioning
confidence: 99%
“…Of the recontacted HFS1 participants, 5,157 participated in HFS2, a response rate of 39.6%. The low response rate for HFS1 may raise concerns about selection bias, but other research has examined the characteristics between the full TTFE population and the participants in both waves of the survey and found few differences between the TTFE population and survey respondents; though survey respondents did have slightly higher incomes than the general TTFE population (Grinstein‐Weiss et al )…”
Section: Experimental Designmentioning
confidence: 99%
“…Given the progressive nature of federal income tax rates and the existence of means‐tested refundable tax credits, such as the Earned Income Tax Credit and the Child Tax Credit, LMI households often count on the annual refund as an important windfall that facilitates major purchases, repayment of debt, and saving (Mendenhall et al ; Smeeding, Phillips, and O'Connor ). Research on LMI tax filers has found that the most common reported usage of the tax refund is to pay down debt; these filers reported that 43% of their tax refund went toward debt repayment, 23% went to immediate consumption, and the remaining third went to savings (Grinstein‐Weiss et al ). This same research found that spending the refund on nonessentials was relatively rare and that the most common reason by far to save the refund was for emergencies, as over three‐fourths of LMI filers who saved the refund did so for emergencies while substantially smaller proportions of filers saved for special purchases or long‐term goals like retirement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation